2016
DOI: 10.1556/2050.2016.0003
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycle effects on jealousy: A study in Curaçao

Abstract: Abstract. Most studies on changes in female behavior and preferences across the menstrual cycle have been conducted in samples comprised of largely white undergraduate students from Western populations. The present study examined cyclical shifts in reactive, preventive and anxious jealousy in a sample of 71 Afro-Caribbean women from Curaçao, a country in the Caribbean. We expected that, because of the risk of conceiving, especially preventive jealousy would be relatively high when fertile to safeguard the male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“… 2. Hypothesis 1 is a replication of Fisher (2004). Hypothesis 2 is a partial replication of Buunk and van Brummen-Girigori (2016), Cobey et al (2012, 2013) and Piccoli et al (2013). Hypothesis 3 is an extension of previous work, as shifts might differ between single and partnered women (Cobey et al, 2013; Fisher & Cox, 2011).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“… 2. Hypothesis 1 is a replication of Fisher (2004). Hypothesis 2 is a partial replication of Buunk and van Brummen-Girigori (2016), Cobey et al (2012, 2013) and Piccoli et al (2013). Hypothesis 3 is an extension of previous work, as shifts might differ between single and partnered women (Cobey et al, 2013; Fisher & Cox, 2011).…”
mentioning
confidence: 90%
“…Findings for shifting jealousy across the ovulatory cycle are even more mixed (Table 2). Three studies reported higher levels of jealousy when women were fertile or when estradiol levels were higher (Buunk & van Brummen-Girigori, 2016; Cobey et al, 2012; Geary et al, 2001). However, other studies did not find any compelling evidence that women’s experienced jealousy changes across the cycle (Arslan et al, 2021) or tracks changes in women’s estradiol and progesterone levels (Hahn et al, 2016, 2020).…”
Section: Introductionmentioning
confidence: 99%